1993
DOI: 10.1093/ejo/15.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Head posture in obstructive sleep apnoea

Abstract: In growing subjects, obstruction of the upper airway may lead to excessive vertical facial development. According to the soft-tissue stretching hypothesis (Solow and Kreiborg, 1977) this could be due to an increased cranio-cervical angulation triggered by the airway obstruction. The present study aimed to examine the effect of airway obstruction on cranio-cervical posture in a sample of adult patients with severe obstructive sleep apnoea (OSA). Lateral cephalometric radiographs taken in the natural head positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 0 publications
8
49
1
3
Order By: Relevance
“…This further shows forward positioning of the head. Similar study found the OPT/CVT to be lesser in the OSAHS group mean 4.5° and SD 2.91 [41]. Similar research found OPT/CVT to be also reduced in the obese OSAHS group (mean 1.1°, SD 2.6), than the control (mean 1.5°, SD 3.1) [42], A comprehensive cephalometric analysis of cranio-cervico-faciohyoid skeletal morphology in 100 male patients with obstructive sleep apnoea (OSA) and 36 male controls was performed, with aberrations in the OSA group features are; shorter dimension of cranial base with slight counter-clockwise rotation and depression of clivus; shorter maxillary length with normal height; maxillomandibular retrognathia related to nasion perpendicular plane (N⊥FH) despite normal angles of prognathism; 47% of the OSA group had mandibular retrognathia; increased anterior lower facial height and mandibular plane angle; reduced size of bony pharynx; inferiorly positioned hyoid bone at C4-C6 level; deviated head posture with larger cranio-cervical angle, and came with the conclusion that cephalometric analysis is highly recommended in OSA patients as one of the most important tools in diagnosis and treatment planning [43].…”
Section: Annals Of Clinical and Laboratory Research Issn 2386-5180supporting
confidence: 65%
“…This further shows forward positioning of the head. Similar study found the OPT/CVT to be lesser in the OSAHS group mean 4.5° and SD 2.91 [41]. Similar research found OPT/CVT to be also reduced in the obese OSAHS group (mean 1.1°, SD 2.6), than the control (mean 1.5°, SD 3.1) [42], A comprehensive cephalometric analysis of cranio-cervico-faciohyoid skeletal morphology in 100 male patients with obstructive sleep apnoea (OSA) and 36 male controls was performed, with aberrations in the OSA group features are; shorter dimension of cranial base with slight counter-clockwise rotation and depression of clivus; shorter maxillary length with normal height; maxillomandibular retrognathia related to nasion perpendicular plane (N⊥FH) despite normal angles of prognathism; 47% of the OSA group had mandibular retrognathia; increased anterior lower facial height and mandibular plane angle; reduced size of bony pharynx; inferiorly positioned hyoid bone at C4-C6 level; deviated head posture with larger cranio-cervical angle, and came with the conclusion that cephalometric analysis is highly recommended in OSA patients as one of the most important tools in diagnosis and treatment planning [43].…”
Section: Annals Of Clinical and Laboratory Research Issn 2386-5180supporting
confidence: 65%
“…As the notochord determines the development of cervical vertebrae and the basilar part of the occipital bone, it also induces the formation of the para-axial mesoderm forming the vertebral arches and the remaining aspect of the occipital bone [4]. Other authors argue that patients with OSA have a more extended head posture as a physiological adaptation to maintain airway patency [8]. However, Svanholt et al [6] revealed that OSA patients with endogenous cervical fusions demonstrated no significant difference in cranial base angle or posture of the head from that of controls.…”
Section: Abnormal Morphologymentioning
confidence: 99%
“…Solow demonstrated that individuals snoring regularly and OSA patients have a deviant posture of their head and neck compared to non-snoring controls [3]. He also pointed out the pressure on the growing facial skeleton by -soft tissue stretching‖ [4].…”
Section: Introductionmentioning
confidence: 99%